2D‐IR spectroscopy: an additional dimension to investigate ultrafast structural dynamics1. (15th May 2013) - Lima, Manuela; Candelaresi, Marco; Foggi, Paolo
Abstract : We describe the theory, some experimental details and the data analysis procedures of two‐dimensional infrared (2D‐IR) spectroscopy. A brief description of an application of the technique to the study of a dipeptide in solution is also reported. Like multi‐dimensional NMR spectroscopy, 2D‐IR can provide additional pieces of information hidden in the inhomogenously broadened bands observed in linear IR spectra. In addition, the presence of off‐diagonal peaks allows a direct estimate of the couplings between vibrational modes. By means of this technique, making use of ultrashort mid‐infrared pulses, exploration of the structure and of the dynamics of molecular systems in the condensed phase and on very short time scales becomes now achievable. The effects of solvent dynamics on Glycine‐L‐Alanine‐Methylamide by 2D‐IR are discussed. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : The theory, the experimental details, and the data analysis of two‐dimensional infrared (2D‐IR) spectroscopy are discussed. An application of the technique to the study of a dipeptide in solution and the effects of solvent dynamics on Glycine‐Alanine‐Methylamide by 2D‐IR are also discussed.